The Optimization of Student Potential through a Learning Design Based on Multiple Intelligences in Elementary Schools - M. Taufik; Reksa Adya Pribadi; Ferah Fairus (Journal of Pedagogy and Education Science, 2026)
Every individual possesses distinct potential and intelligence, necessitating the design of basic-level learning to accommodate these differences. A learning design based on multiple intelligences has become one way to optimize students' potential. From the results of a preliminary study, there are schools that have implemented learning practices based on Multiple Intelligences to reduce uniformity in the learning system. This study aims to describe the optimization of students' potential through a learning design based on multiple intelligences at SDIU Cahaya Al-Fatih. This research employs a qualitative approach with a case study design at Elementary School Cahaya Al-Fatih in Pandeglang District. In-depth interviews were conducted with the principal, teachers, and several students. Participatory observation was carried out in classrooms and school environments, as well as during the learning activities. Lastly, documentation was used to collect data. The study reveals that the theory of Multiple Intelligences at School begins with a systematic approach, starting from student profile assessments, the design of diverse curricula and lesson plans, the implementation of active project-based learning, and continuous evaluation. This demonstrates that education can shift its focus from logical-mathematical and linguistic intelligences to recognizing and appreciating other types of intelligence, such as musical, kinesthetic, and interpersonal intelligence. However, as a consideration or recommendation, schools need to remain consistent in developing teacher training, establish specific assessment standards or rubrics, and ensure a balance between developing students' dominant intelligences and nurturing other potentially dormant intelligences.